Modul “Gen Positif” untuk Meningkatkan Pengetahuan Regulasi Emosi Takut Gagal Siswa Remaja Awal - Astiti Tenriawaru Ahmad; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Early adolescents need adaptation in various aspects including in the process of achievement of academic achievement. The difficulties encountered in achieving goals in the academic field caused early adolescents to develop a fear of failure. Individuals will try to avoid failure by determining their goals far below its potential, feel anxious, and not motivated in learning. This emotion can be a serious problem if it is not regulated in an adaptive way. Therefore early adolescents need knowledge of how to regulate the emotions of fear of failure. This study aims to validate the module